Evaluation of Online Biology Learning in Indonesia Based on The Technology Acceptance Model (TAM) - Marini Alif Afifa; Muji Sri Prastiwi (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
This research aims to evaluate online biology learning in Indonesia based on the technology acceptance model (TAM), which includes ease, usefulness, attitude, and intention to use technology. This research was interpreted in descriptive quantitative using a survey method with the research sample of biology teachers and high school students throughout Indonesia who had done online biology learning. The results show that biology teachers and high school students agree that online biology learning with the Learning Management System using Google Classroom, social media using WhatsApp, and video conference using Zoom Meetings is easy to use and has beneficial functions for users in online learning. Online biology learning using Google Classroom, WhatsApp, and Zoom meetings is acceptable and suitable as software for learning biology.